Russian federation : Social Expenditure and Fiscal Federalism in Russia - World Bank (World Bank, 2012)
The Russia Social Expenditure Review (SER) has been undertaken by the human development team in the Europe and Central Asia Region of the World Bank at the request of the Ministry of Finance of the Russian Federation. This Report presents the key findings of the Russia SER work. The key objectives of the SER are to: 1) benchmark Russia's social spending and some human development outcomes to those in Organization for Economic Co-operation and Development (OECD) countries; 2) present a topology of Russia's regions in terms of spending efficiency in health and education; 3) identify options for achieving higher levels of efficiency in public spending on health and education; and 4) analyze the system of inter-budgetary transfers in the framework of delivery of social services, and suggest options for improvements in this system. The findings presented in the report are not intended as normative statements on what should be the right levels of spending or the right composition of spending in Russia or its regions. The analysis of social sector spending is undertaken keeping in mind that efficiency and equity considerations are closely linked to institutional changes in the policy environment. The public spending efficiency reforms are indeed quite high on the policy agenda in Russia, but they are implemented unevenly across regions.